The anti-staphylococcal activity (planktonic and biofilm) of Cnestis ferruginea is due to benzoquinone, the oxidation product of hydroquinone - Panda, Sujogya Kumar; Reynders, Michelle; Kipanga, Purity N.; Luyten, Walter (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCnestis ferruginea is used frequently in African traditional medicine for treating infectious diseases. Previous bioassay-guided purification has identified hydroquinone as the major bio-active compound in the aforementioned plant, responsible for its antibacterial activity against Staphylococcus aureus. While the phenol hydroquinone can be directly extracted from the plant, it may undergo (reversible) oxidation under mild conditions to yield benzoquinone, a compound with known antimicrobial activity against i.a. S. aureus.MethodsWe, examined whether hydroquinone or its oxidation product, benzoquinone, is the active compound against bacteria such as S. aureus. To achieve this we performed broth microdilution (planktonic) and biofilm activity tests against two different strains of S. aureus. The inhibitory concentrations (IC50) of benzoquinone and hydroquinone under various circumstances were compared, assessing their stability, and examining their effectiveness against two strains of S. aureus (Rosenbach and USA 300) in both planktonic and biofilm environments.ResultsBenzoquinone demonstrated antibacterial activity against S. aureus Rosenbach and USA 300 with IC50 of 6.90 ± 2.30 mM and 7.72 ± 2.73 mM, respectively, while the corresponding values for hydroquinone were 15.63 ± 2.62 mM and 19.21 ± 4.84 mM, respectively. However, when oxidation was prevented by the addition of antioxidants such as ascorbic acid or glutathione, hydroquinone lost its antibacterial property, while benzoquinone retained activity. Comparing conditions in which hydroquinone could convert into benzoquinone against conditions in which this conversion was inhibited, showed that hydroquinone alone did not inhibit bacterial growth of S. aureus, while benzoquinone alone did.DiscussionThese results prove that the oxidation product benzoquinone is responsible for the antimicrobial activity previously ascribed to hydroquinone.